Not everything is as it seems: constitutional control via amparo against fraudulent arbitrations - Pierantoni Salazar, Gian Piero (2025)
Peruvian law safeguards the arbitral institution through principles that prevent judicial interferences in the arbitrator’s functions, who are empowered to rule on their own jurisdiction and to reject any intrusion from ordinary courts. Furthermore, the Arbitration Law (Legislative Decree 1071) stipulates that any review of the validity of arbitral proceedings must occur only after the issuance of the final award, and that the ordinary annulment procedure is equally effective as the constitutional amparo via. Binding precedents confirm this.Exploiting the protection afforded to arbitrations in Peru, certain actors simulate ‘arbitrations’ to divert victims into a sham ‘proceeding’, without any valid arbitration agreement that sustains it. These ‘arbitrations’ involve collusion among ‘claimant’, ‘arbitrator’ and ‘arbitration center’ to issue a document labeled as ‘award’ with the sole intent of obtaining unjust enrichment at the victim’s expense. These are known as ‘fraudulent arbitrations’.This article examines whether it is legally and constitutionally viable to file an amparo action prior to the issuance of the ‘award’ in a fraudulent arbitration.